2019
DOI: 10.2217/ijh-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Inhibition of PD-L1 and CTLA-4 in a Child with Refractory Acute Leukemia

Abstract: Children with multiple relapsed or refractory leukemia have dismal survival. Research has identified engagement of immune checkpoint receptors (e.g., PD-1, PD-L1 and CTLA-4) as a mechanism for treatment resistance. For adult cancer, inhibitors of PD-1 (nivolumab) and CTLA-4 (ipilimumab) have shown promise with response rates ranging from 7 to 40%. In vitro studies using acute myeloid leukemia cell lines have shown that acute myeloid leukemia blasts may similarly utilize the PD-1/PD-L1 axis to evade an anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…AL, a hematopoietic stem cell malignant clonal disease, often occurs in children under 15 years of age 151617. Children with refractory AL have a low survival rate 18. To date, chemotherapy remains the primary treatment method for leukemia; however, a large number of patients experience poor responses to chemotherapy 1920.…”
Section: Discussionmentioning
confidence: 99%
“…AL, a hematopoietic stem cell malignant clonal disease, often occurs in children under 15 years of age 151617. Children with refractory AL have a low survival rate 18. To date, chemotherapy remains the primary treatment method for leukemia; however, a large number of patients experience poor responses to chemotherapy 1920.…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab has also been successfully used in adults who relapse following SCT to regain donor chimerism without the need for second transplant [ 60 ]. The only reported use in pediatric AML was in a child with highly refractory relapsed AML in combination with azacitidine in which the child had symptomatic relief after therapy but failed to have any significant improvement in disease burden, though phase I/II clinical trials in children with AML have recently begun (NCT03825367) [ 61 ].…”
Section: New Therapymentioning
confidence: 99%
“…Moreover, the combination of azacytidine and PD‐1/PD‐L1 inhibition was also used for AML treatment. More recently, it was reported that PD‐1 (nivolumab) and CTLA‐4 (ipilimumab) combined with 5‐azacytidine was used to treat multiple relapsed/refractory leukemia pediatric patients and improve clinical outcome …”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was reported that PD-1 (nivolumab) and CTLA-4 (ipilimumab) combined with 5-azacytidine was used to treat multiple relapsed/refractory leukemia pediatric patients and improve clinical outcome. 24,25 Previous studies have shown an increase in PD-1 + /Tim-3 + T cells, particularly PD-1 + CD8 + exhausted T cells, in patients with AML; however, the changes in different cases appeared to be relatively different; therefore, it leads to consider whether immune suppression in leukemia patients may be involved in different alteration patterns of immune checkpoints. For example, significantly higher Tim-3 + T cells in BM may be a reason for the failure to respond to PD-1 inhibitors in a subset of MM patients.…”
Section: Introductionmentioning
confidence: 99%